Marine Resources to Indonesia's Food Security Potential - Budi Rusdianto; Nuri Rahayu Ningsih; Rusiadi; Diwayana Putri Nasution; Suhendi; Andria Zulfa; Lia Nazliana Nasution; Bakhtiar Efendi (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
The huge economic potential of the ocean in Indonesia and the importance of maintaining the sustainability of marine resource exploitation to support sustainable economic growth and food security. As one of the potentials in the marine and fisheries sector, the estimated potential of fish resources from marine capture fisheries and aquaculture certainly has the potential to fulfill the food of the Indonesian people with high protein nutritional value. The purpose of this research is to see the potential of the marine sector for food security in Indonesia. This type of research is quantitative descriptive research with time series data from 2017 to 2022 obtained from the Indonesian Central Bureau of Statistics. This research is located in Indonesia. The results showed that the water sector, namely fisheries, has high potential to support food security in Indonesia. In addition to the nutritional content contained in fish that is easily digested by the body, the selling price of fish also varies so that it is affordable at all economic levels of Indonesian households.